Apartheid’s Patriarchies in Decline: White Masculinities in Damon Galgut’s The Promise - Carolin, Andy (Journal of Literary Studies)
The initial popular reception of Damon Galgut’s The Promise (2021) has overlooked issues of gender in the text, favouring instead the more narrow allegorical readings of race. In response to this, this article emphasises the novel’s engagement with the distinctly gendered nature of the transition from apartheid, focusing on the representation of white masculinities in the text. This article raises concerns about how these masculinities are depicted. Through close engagement with the text’s systematic introduction and disavowal of the constitutive forces of apartheid’s patriarchies—including fatherhood, Christianity, and the security state—this article argues that the novel’s engagement with white masculinities is one of negation; it offers a narrative mode in which white masculinities are rendered sterile, rewritten in the well-worn register of an anti-apartheid moral certitude that depends on tired tropes. While the novel attempts an important decentring of white masculinities, its outlook is ultimately bleak as white masculinities are shown to lack depth, resulting in their power in the present being curiously absented in an act of textual erasure.